Bisexuality, religion and spirituality : critical perspectives - Yip, Andrew K. T., 1963-; Toft, Alex (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book brings together the work of an international team of experts investigating the intersection of bisexuality, religion and spirituality. Drawing from disciplines such as sociology, psychology, theology, religious studies, and literary studies, it critically examines, both theoretically and empirically, the lived experiences of bisexual people of diverse religious faiths and spiritualities, in the context of UK, Canada, Lebanon, Turkey, Australia, and the USA. As an important and insightful exploration of an under-researched and often misunderstood minority, this book will appeal to scholars across the social sciences with interests in sexuality, religion, spirituality and identity"--
OCLC-licensed vendor bibliographic record.
Keywords: Bisexuality -- Religious aspects; Bisexuals -- Religious life; Spiritual life; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General